Ghrelin has both indirect and direct inhibiting effect on GnRH neurons: Reply for letter to editor Ghrelin directly affects GnRH neurons - Celik, Onder; Aydin, Suleyman; Celik, Nilufer; Yilmaz, Musa (Elsevier Science Inc, 2016)
[Abstract Not Available]
Keywords: Gonadotropin-Releasing-Hormone; Luteinizing-Hormone; Growth-Hormone; Female Rats; Suppresses Secretion; Delayed Menarche; Puberty Onset; in-Vitro; Leptin; Receptor